Dynamic and ambidextrous: international expansion of digital economy ventures from an emerging market - DÜLGER TAŞKIN, AYŞE MERAL (My University, 2022)
Purpose This study aims to explore the internationalization trajectory of emerging country digital economy ventures by specifically concentrating on how ambidexterity facilitates international market expansion. Further, this paper examines how these ventures develop dynamic capabilities by using their ambidextrous skills in the entrepreneurial ecosystem (EE). Design/methodology/approach This study adopts a multiple-case research design where data were gathered from five digital economy ventures in Turkey, serving an international array of customers. Findings The analyses reveal that, to a large extent, internationalization is enabled by the extensive use of ambidextrous skills in the ecosystem domain. We found evidence for practicing exploration and exploitation while interacting with several ecosystem pillars grouped as founder-related, firm-related and business context-related factors. These interactions portray how ventures sense, seize and transform resources to support their international expansion. Originality/value This study extends the current literature on internationalization by discussing the role of ambidexterity as a dynamic capability. The findings also demonstrate the EE as a construct to explain international entrepreneurial activity. Further, the study extends the existing literature by considering the calls for research on dynamic capabilities of international new ventures (INVs). Finally, the findings point to several implications both for practitioners and policymakers.
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Social Sciences and Humanities; Management; İŞLETME; Ekonomi ve İş; Sosyal Bilimler (SOC); BUSINESS; ECONOMICS & BUSINESS; Social Sciences (SOC); Strateji ve Yönetim; Genel İşletme, Yönetim ve Muhasebe; İşletme ve Uluslararası Yönetim; Pazarlama; Sosyal Bilimler ve Beşeri Bilimler; Strategy and Management; General Business, Management and Accounting; Business and International Management; Marketing; Social Sciences & Humanities; Ambidexterity; Dynamic capabilities; International new ventures; Entrepreneurial ecosystem; Digital economy ventures; Emerging market; BORN GLOBAL FIRM; RESOURCE-BASED VIEW; ORGANIZATIONAL AMBIDEXTERITY; ENTREPRENEURIAL ECOSYSTEMS; CAPABILITIES; EXPLOITATION; EXPLORATION; PERSPECTIVE; MODEL; OPPORTUNITIES; Ambidexterity; Dynamic capabilities; International new ventures; Entrepreneurial ecosystem; Digital economy ventures; Emerging market